Targeting Ideal Dual‐Absorber Tandem Water Splitting Using Perovskite Photovoltaics and CuInxGa1‐xSe2 Photocathodes. Issue 24 (20th October 2015) - Luo, Jingshan; Li, Zhen; Nishiwaki, Shiro; Schreier, Marcel; Mayer, Matthew T.; Cendula, Peter; Lee, Yong Hui; Fu, Kunwu; Cao, Anyuan; Nazeeruddin, Mohammad Khaja; Romanyuk, Yaroslav E.; Buecheler, Stephan; et al.
Abstract : Efficient sunlight‐driven water splitting devices can be achieved by pairing two absorbers of different optimized bandgaps in an optical tandem design. With tunable absorption ranges and cell voltages, organic–inorganic metal halide perovskite solar cells provide new opportunities for tailoring top absorbers for such devices. In this work, semitransparent perovskite solar cells are developed for use as the top cell in tandem with a smaller bandgap photocathode to enable panchromatic harvesting of the solar spectrum. A new CuIn x Ga1‐ x Se2 multilayer photocathode is designed, exhibiting excellent performance for photoelectrochemical water reduction and representing a near‐ideal bottom absorber. When pairing it below a semitransparent CH3 NH3 PbBr3 ‐based solar cell, a solar‐to‐hydrogen efficiency exceeding 6% is achieved, the highest value yet reported for a photovoltaic–photoelectrochemical device utilizing a single‐junction solar cell as the bias source under one sun illumination. The analysis shows that the efficiency can reach more than 20% through further optimization of the perovskite top absorber. Abstract : An ideal dual‐absorber tandem solar water splitting device consists of a top absorber of around 1.7 eV bandgap paired above a 1.0 eV bandgap bottom absorber. A high‐performance CuIn x Ga1‐ x Se2 photocathode accomplishes the latter requirement, allowing exploration of bandgap variation of perovskite top absorbers toward targeting the ideal tandem performance.